Sikap Percaya Diri Anak Didik dalam Eksperimentasi Model Pembelajaran Kooperatif Tipe Think, Pair, Share (TPS) - Maghfiroh Yanuarti (UIN Raden Mas Said Surakarta, 2018)
This research is an experimental research that aims to get the condition and description about whether the type of learning Think, Pair, and Share (TPS) and confidence in learning has a positive correlation to the attitude of learning of students to the subjects of Mathematics. This research is a quasi experimental research with 3x3 factorial design towards 302 students from SMPN 3 Kartasura, SMPN 2 Kartasura, and SMPN 2 Tray taken stratified cluster random sampling. Instruments used to collect data are student achievement test and confidence questionnaire questionnaire. The results show that mathematics learning achievement using cooperative learning model of TPS type has better achievement compared with using conventional learning model learning model. Students with a high level of confidence, in the implementation of TPS learning achieve a better level of learning achievement than conventional learning models. In addition, the results of this study also indicate that the potential students such as confidence have an effect on student achievement.